Alzheimer's disease models and functional genomics—How many needles are there in the haystack? - Gotz, Jurgen; Matamales, Miriam; Gotz, Naeman; Ittner, Lars M.; Eckert, Anne (Frontiers in Physiology, 2012)
Alzheimer's disease (AD) and frontotemporal lobar degeneration (FTLD) are complex human brain disorders that affect an increasing number of people worldwide. With the identification first of the proteins that aggregate in AD and FTLD brains and subsequently of pathogenic gene mutations that cause their formation in the familial cases, the foundation was laid for the generation of animal models. These recapitulate essential aspects of the human conditions; expression of mutant forms of the amyloid-β protein-encoding APP gene in mice reproduces amyloid-β (Aβ) plaque formation in AD, while that of mutant forms of the tau-encoding MAPT gene reproduces tau-containing neurofibrillary tangle formation, a lesion that is also prevalent in FTLD-Tau. The mouse models have been complemented by those in lower species such as C. elegans or Drosophila, highlighting the crucial role for Aβ and tau in human neurodegenerative disease. In this review, we will introduce selected AD/FTLD models and discuss how they were instrumental, by identifying deregulated mRNAs, miRNAs and proteins, in dissecting pathogenic mechanisms in neurodegenerative disease. We will discuss some recent examples, which includes miRNA species that are specifically deregulated by Aβ, mitochondrial proteins that are targets of both Aβ and tau, and the nuclear splicing factor SFPQ that accumulates in the cytoplasm in a tau-dependent manner. These examples illustrate how a functional genomics approach followed by a careful validation in experimental models and human tissue leads to a deeper understanding of the pathogenesis of AD and FTLD and ultimately, may help in finding a cure.